2020
DOI: 10.3390/app10207068
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Fault Diagnosis Method Using Acoustic Emission Signals for Bearings under Complex Working Conditions

Abstract: Recent convolutional neural network (CNN) models in image processing can be used as feature-extraction methods to achieve high accuracy as well as automatic processing in bearing fault diagnosis. The combination of deep learning methods with appropriate signal representation techniques has proven its efficiency compared with traditional algorithms. Vital electrical machines require a strict monitoring system, and the accuracy of these machines’ monitoring systems takes precedence over any other factors. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…To verify the efficiency and accuracy of the proposed models, we use the AE signal dataset used in the literature [8], [11], [48]- [50]. We initially evaluate the proposed process's efficiency by metrics of the number of MAC, the number of parameters, and latency in various cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the efficiency and accuracy of the proposed models, we use the AE signal dataset used in the literature [8], [11], [48]- [50]. We initially evaluate the proposed process's efficiency by metrics of the number of MAC, the number of parameters, and latency in various cases.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al proposed a transfer learning from AlexNet (2-D CNN) with input images generated from eight different time-frequency analysis methods [11]. Similarly, Tuan et al showed the effectiveness of timefrequency representation; they utilized VGGNet and EfficientNet with a 2-D spectrogram to achieve high accuracy in complicated bearing faults classification [8] [9]. However, a downside of CNN-based methods in the BFD field is the high overhead of computational resources compared with common traditional methods [11].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, on the one hand, ref. [155] proposes a CNN-based classification method for diagnosing bearing faults under variable shaft speeds using acoustic signals. These signals are represented by spectrograms to obtain as much information as possible in the time-frequency domain.…”
Section: Mechanical Subsystemmentioning
confidence: 99%
“…In general, the diagnosis issues are solved by modeling the physical model bearing or finding the relationship between bearing defects and the corresponding characteristic of monitoring signals that carry the bearing health information. Various modalities have been utilized for monitoring bearings-such as vibration [2][3][4][5], stator current [6,7], thermal imaging [8], electromagnetic signals [9], and acoustic emission (AE) [10][11][12][13]. In general, these methods are categorized into knowledge-based, physical model-based, and data-driven approaches, with the help of signal processing analysis in the time-, frequency-, or time-frequency domains.…”
Section: Introductionmentioning
confidence: 99%
“…M.T. Pham et al [10] proposed a method based on the efficient-net (CNN) to predict not only bearing fault types but also the level of degradation, but the proposed multiclass classification shapes a network with many classes. This method requires a large amount of computational resources.…”
Section: Introductionmentioning
confidence: 99%